2008
DOI: 10.1186/bcr2105
|View full text |Cite
|
Sign up to set email alerts
|

Jab1 is a target of EGFR signaling in ERα-negative breast cancer

Abstract: Introduction c-Jun activation domain-binding protein-1 (Jab1) is a multifunctional signaling protein that previously has been shown to be a master regulator of a poor prognostic gene signature in invasive breast cancer and to mediate the action of S100A7. Since epidermal growth factor receptor (EGFR), like S100A7, is often expressed in estrogen receptor-alphanegative (ERα -) breast cancer, we set out to investigate the role of Jab1 in mediating EGFR signaling, another facet of the ERα -phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 44 publications
2
34
0
Order By: Relevance
“…We show that Psor was required for the pro-invasive activity of avb6 and that disruption of the association of Psor with the b6 cytoplasmic tail inhibited invasion of oral SCC cells. Previously avb6 and Psor have been implicated independently in carcinoma progression and invasion (Breuss et al, 1995;Clark et al, 1996;Haapasalmi et al, 1996;Larjava et al, 1996;Jones et al, 1997;Al-Haddad et al, 1999;Regezi et al, 2002;Jiang et al, 2004;Emberley et al, 2004;Krop et al, 2005;Banerjee et al, 2005;Ralhan et al, 2008;Wang et al, 2008;Paruchuri et al, 2008;Kesting et al, 2009), and our data identify a novel pro-invasive interaction that may explain some of these previous observations. The data further suggest that inhibition of this b6-Psor association may provide a novel therapeutic target to inhibit carcinoma invasion.…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…We show that Psor was required for the pro-invasive activity of avb6 and that disruption of the association of Psor with the b6 cytoplasmic tail inhibited invasion of oral SCC cells. Previously avb6 and Psor have been implicated independently in carcinoma progression and invasion (Breuss et al, 1995;Clark et al, 1996;Haapasalmi et al, 1996;Larjava et al, 1996;Jones et al, 1997;Al-Haddad et al, 1999;Regezi et al, 2002;Jiang et al, 2004;Emberley et al, 2004;Krop et al, 2005;Banerjee et al, 2005;Ralhan et al, 2008;Wang et al, 2008;Paruchuri et al, 2008;Kesting et al, 2009), and our data identify a novel pro-invasive interaction that may explain some of these previous observations. The data further suggest that inhibition of this b6-Psor association may provide a novel therapeutic target to inhibit carcinoma invasion.…”
Section: Introductionsupporting
confidence: 72%
“…Interestingly, like avb6, psoriasin expression has been reported to be up-regulated in epithelial cells of various oral squamous carcinomas (Banerjee et al, 2005;Zhou et al, 2008;Ralhan et al, 2008;Kesting et al, 2009) and subsets of breast cancers (Al-Haddad et al, 1999;Jiang et al, 2004;Emberley et al, 2004Emberley et al, , 2005Krop et al, 2005;Petersson et al, 2007;Wang et al, 2008;Paruchuri et al, 2008). The precise role of Psor in tumour behaviour is, however, unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our data are preliminary this is intriguing, given previous observations that S100A7 itself may promote EGF expression and is involved in EGFR signaling (Emberley et al, 2005;Paruchuri et al, 2008;Wang et al, 2008). We have confirmed by analysis of expression levels in an independent breast tumor data set (UNC) that S100A7 correlates with EGFR expression in a large unselected cohort and within the ER-negative subset, supporting the existence of functional cooperativity between S100A7 and EGFR (Supplementary Table S2).…”
Section: Inflammatory Cytokines Induce S100a7 Expression In Breast Cellssupporting
confidence: 58%
“…Thus, activation of PI3K, ERK1/2 and STAT3 all appear to be necessary for full S100A7 induction by OSM or IL-6. We (Emberley et al, 2005;Wang et al, 2008) and others (Paruchuri et al, 2008) have previously shown a link between S100A7 and the epidermal growth factor (EGF) pathway. IL-6 and EGF signaling can also be functionally linked (Badache and Hynes, 2001).…”
Section: Inflammatory Cytokines Induce S100a7 Expression In Breast Cellsmentioning
confidence: 99%